From peak to plummet: impending decline of the warm Arctic-cold continents phenomenon - Yungi Hong; S.-Y. Simon Wang; Seok-Woo Son; Jee-Hoon Jeong; Sang-Woo Kim; Baekmin Kim; Hyungjun Kim; Jin-Ho Yoon (npj Climate and Atmospheric Science, 2024)
Abstract This study assesses the projected trajectory of Warm Arctic-Cold Continent (WACC) events in East Asia and North America through large ensemble simulation for the upcoming decades. It analyses the evolution of the geographical boundaries of threshold cold temperatures, revealing a significant northward shift as a sign of global warming’s impact on the southward advancement of Arctic cold air. While validating the intensification of the WACC phenomenon until the 2020 s, echoing earlier studies, the findings indicate a marked decrease beginning in the 2030s. If warming is not curbed, this shift suggests a critical modification in the WACC pattern, prompting a re-evaluation of existing theories and models for extreme winter weather events. The results have major implications, spurring communities impacted by WACC to anticipate future changes and encouraging the climate forecasting community to update conceptual models for improved adaptation and mitigation approaches.